Tingkat Pengetahuan Masyarakat Mengenai Sanitasi Lingkungan di Kecamatan Masbagik Kabupaten Lombok Timur Provinsi Nusa Tenggara Barat - Baiq Liana Widiyanti; Ig. L. Setyawan Purnama; Adi Heru Sutomo; Setiadi Setiadi (Geodika: Jurnal Kajian Ilmu dan Pendidikan Geografi, 2017)
Community empowerment in health fieldwas an effort to provide power or strengthening the community to care and engage in the implementation of health efforts and healthy behavior through the process of providing information to individuals, families or groups continuously in order to make the change from knowledge, attitude and action aspects. The basis for behavior change is the aspect of knowledge. The purpose of this research is to know the level of public knowledge about environmental sanitation. The type of research is descriptive with survey design using cross sectional time approach. The results showed that in general the level of knowledge of people in the study area was good categorized. The dominant factors that influence the level of public knowledge about environmental sanitation are: education, age, occupation, income and information. To improve the knowledge of the community, the information factor should get priority in educating the public regarding health promotion programs. Mass media utilizing local culture aspect is the right choice to provide information in improving community knowledge related to environmental sanitation.